Antioxidant activity and physicochemical properties of mango nectar with pitahaya - Vera, Jorge; Moreira, Neycer; Muñoz, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Currently, mixed fruit nectars are generating greater consumer interest due to their potential contribution of nutrients and exotic flavors. The objective of the study was to evaluate the antioxidant activity and physicochemical properties of mango nectar (Mangifera indica L.) made with various levels of pitahaya (Hylocereus undatus). A completely randomized experimental design was used. The test consisted of the formulation of three treatments (10, 20, and 30 % pitahaya flesh (pf) and a control). Physicochemical, functional, microbiological, and sensory parameters were evaluated. Analysis of variance and Dunnett and Kruskal Wallis mean comparison test were applied at 5 % significance. The results showed that the levels of pitahaya flesh significantly influenced the response variables of pH, viscosity, soluble solids, density, turbidity, antioxidant activity, and total phenols, on the contrary, the colorimetry parameters (L, a, b) presented a p> 0.05. Regarding sensorial acceptability, a p < 0.05 was determined in the attributes of texture, consistency, and flavor, while color and smell were not significant (p>0.05). The treatments under study met the physicochemical and microbiological requirements established in the NTE INEN 2337 standard. It was shown that the addition of 30 % of pf improved the content of total phenols in mango nectar up to 0.537 ± 0.00 mg Gallic Acid Equivalent.mL-1. The nectars had a yellow color with a greenish hue and bright luminosity. The treatment T3 was considered the best at the organoleptic level in texture, consistency, and flavor.